PERLAKUAN TERHADAP TERPIDANA MATI DI LEMBAGA PEMASYARAKATAN DALAM PERSPEKTIF HAK ASASI MANUSIA - Sitanggang, Djernih; Laela Fakhriah, Efa; Suseno, Sigid (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2018)
The Penal system is conducted by the correctional facility was only oriented towards convicted criminals. The problem was on how to treat death penalty convicts who are in the penitentiary during the execution waiting period. The result research’s on Penal system is only effective for convicts obliged to follow the restoration program, whereas the death penalty convict was not obliged and for him to decide actively or not to follow the restoration program. The restoration program must to be obliged for the death penalty convict, so that the penal system could provide protection for Human Rights